Digital Music Composition in the Soundscape Concept of ISI Padang Panjang - Sukria, Eki; Murniati, Murniati; Sina, Ibnu; Hendri, Yon; wijaksana, Bambang (Institut Seni Indonesia Padangpanjang, 2024)
The ISI Padangpanjang Sounds work is a digital music composition with a soundscape concept created from the sounds of activities around the ISI Padangpanjang campus which were recorded using the Zoom H1n Handy Recorder mic device. The sound recordings of activities and objects around the campus will be sampled and processed using Digital Audio Work Station (DAW) Studio One 5. This work tells about activities on the ISI Padang Panjang campus. On this campus there are two faculties, namely the performing arts faculty and the fine arts and design faculty. In the Suara ISI Padangpanjang work there are 3 parts with a duration of 7.10 minutes, the first part is morning activities, the second part is afternoon activities and the third part is evening activities which closes with afternoon activities. the sound of the Isha call to prayer at the end.